Chronic ankle instability modifies proximal lower extremity biomechanics during sports maneuvers that may increase the risk of ACL injury: A systematic review - Xu, Y.; Song, B.; Ming, A.; Zhang, C.; Ni, G. (Frontiers in Physiology, 2022)
The biomechanical changes in the lower extremity caused by chronic ankle instability (CAI) are not restricted to the ankle joint, but also affect the proximal joints, increasing the risk of joint injury. This study aimed to systematically review the research on CAI and lower extremity angle and movements during side-cutting, stop jumping, and landing tasks, to provide a systematic and basic theoretical basis for preventing lower extremity injury. Literature published from exception to April 2022 were searched in the PubMed, Web of Science, and SPORTDiscus databases using the keywords of "chronic ankle instability," "side-cut," "stop jump," and "landing." Only studies that compared participants with chronic ankle instability with healthy participants and assessed lower extremity kinetics or kinematics during side-cutting, stop jumping, or landing were included. The risk of bias assessment was conducted using a modified version of the Newcastle-Ottawa checklist. After title, abstract, and full text screening, 32 studies were included and the average score of the quality evaluation was 7 points (range 6-8). Among them five studies were related to the side-cut task, three studies were the stop-jump task, and twenty-four studies were related to landing. Although the results of many studies are inconsistent, participants with CAI exhibit altered lower extremity proximal joint movement strategies during side cut, stop jump, and landings, however, such alterations may increase the risk of anterior cruciate ligament injury.